2013
DOI: 10.1111/all.12175
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acids up‐regulate functional eosinophil‐driving receptor CCR3

Abstract: Eotaxins and their receptor CCR3 have a definitive role for tissue accumulation of eosinophils both under homeostatic and pathologic conditions. However, physiological stimuli that can up-regulate CCR3 in blood-derived human eosinophils have not been recognized. As a prior gene microarray study revealed up-regulation of CCR3 in eosinophils stimulated with retinoic acids (RAs), the expression of functional CCR3 was examined. We found that 9-cis RA and all-trans RA (ATRA) significantly induced surface CCR3 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Since the majority of eosinophils normally reside within mucosal tissues interfacing with the environment [42, 43], it is conceivable that crosslinking of IgA receptors induces EETosis and contributes to mucosal immunity. High concentration of monosodium urate induces rapid eosinophil death [44] and DNA traps [45], suggesting that endogenous danger signals also elicit EETosis.…”
Section: Eosinophil Etosismentioning
confidence: 99%
“…Since the majority of eosinophils normally reside within mucosal tissues interfacing with the environment [42, 43], it is conceivable that crosslinking of IgA receptors induces EETosis and contributes to mucosal immunity. High concentration of monosodium urate induces rapid eosinophil death [44] and DNA traps [45], suggesting that endogenous danger signals also elicit EETosis.…”
Section: Eosinophil Etosismentioning
confidence: 99%
“…Molecular complexes between β-lg and retinoids provoke inflammation and hypersensitivity due to interactions with the transient receptor potential channel vanilloid subtype 1 (TRPV1) (Yin et al, 2013). Moreover, these protein domains up-regulate the eosinophil-driving receptor CCR3 (Ueki et al, 2013). These characteristics indicate that the digestion of β-lg is a key process in food tolerance and allergenicity.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…In a series in our previous study, we found that naturally occurring retinoids, retinoic acids ( RAs ), elicit CCR 3 expression on human blood eosinophils. 2 Peripheral blood eosinophils constitutively express nuclear receptors for retinoids, RA receptor ( RAR) -α, -β, and -γ, and retinoid X receptor (RXR)-α and -β. 3 Using a gene microarray, we have screened up-regulation of CCR3 transcription in RAstimulated eosinophils.…”
mentioning
confidence: 99%
“…Furthermore, RA-induced CCR3 leads to enhanced functional capacities in terms of calcium signaling and chemotactic responses. 2 Surprisingly, RAs are the first recognized physiological CCR3 upregulator in mature human eosinophils despite the recent progress in eosinophil biology.…”
mentioning
confidence: 99%
See 1 more Smart Citation